Gender and extreme metal: Understanding gender relations in the Montreal extreme metal scene with schipper's gender framework - Beauchamp, Caroline (Université Concordia, 2021)
Extreme metal is a masculine space, yet more and more women join in. They face a contradiction: as women, they are expected to adopt feminine behaviours; however, they are part of a subculture that valorizes warrior masculinity. I sought to understand the gender expectations of the Montreal extreme metal scene and interpret the contradictions encountered by women in this scene with the help of Schippers’ (2007) theoretical framework on gender. To do so, I conducted 16 individual interviews with women and men who take part in the scene. This research fills a gap in the literature on gender that derives from Connell and Schippers’ writings and addresses issues that the field of metal studies has brushed over. I found that metal men are the “default” participants in the scene. They are expected to be fine music connoisseurs and even become musicians. In contrast, women’s presence is heterosexualized and attributed to a romantic or sexual interest in metal men. Women are suspected of being “poseuses” or groupies with no real interest in the music until proven otherwise. To become legitimate participants, they have to overcome those expectations and prove that they are worthy of being viewed through the prism of masculinity rather than femininity. They do so by proving their exceptionality through manhood acts and distancing themselves from other women. Despite their gender transgressions, women’s presence does not fundamentally question gender relations but reaffirms the overall primacy of masculinity over femininity.
https://spectrum.library.concordia.ca/id/eprint/988125/
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; anthropologie; approches et analyses; discipline; genre; hétérosexisme; masculinité; montréal; mémoires/thèses; privilèges; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; stéréotypes de genre; systèmes d'oppressions; étude qualitative